ZINNER SYNDROME - Stavreski, Nacko; Petrovski, Aleksandar; Jovanovska, Elizabeta Stojovska; Ilievski, Mitko; Zafirova, Biljana (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Developmental malformations of the urogenital tract are rare, and most of them are cystic anomalies. In the embryogenesis, exactly during the first trimester of gestation developmental arrest affecting mesonephric (Wolffian) duct results in unilateral renal agenesis. Ipsilateral seminal vesicle cyst also affecting the caudal end of Mullerian duct produces ipsilateral ejaculatory duct obstruction. Most of the patients with this malformation are asymptomatic until the 2 nd or 3 rd decade of life. Initially, majority of patients have nonspecific symptoms such as perineal discomfort, urinary urgency, prostatism, painful ejaculation and dysuria. We report an uncommon case of a 24-year-old patient presented with symptoms of lower urinary tract irritation. Radiologic imaging modalities as ultrasonography, contrast-enhanced computed tomography and magnetic resonance imaging are all helpful in diagnosis of this extremely rare developmental anomaly. Keywords: MRI, seminal vesicles, ejaculatory duct, CT. https://doi.org/10.55302/JMS2143171s